Physicochemical Properties And Sensory Evaluation Of Fermented Mustard With Difference Ratio Of Rice Water And Tal Palm Sap - Nur Agustin Mardiana; Domas Patria Galih; Sutrisno Adi Prayitno; Chusnul Chotimah (OJS Universitas Muhammadiyah Gresik, 2021)
Tal palm plant is widely known and spread in Indonesia. However, the application of tal palm plant especially sap as another product is limited. Tal plant sap used in mustard fermentation as carbon source with rice water. The aim of this study is to find suitable ratio of rice water and tal palm sap for the best physicochemical properties and sensory characteristic of fermented mustard. This experiment was using completely randomized design with one factor and 5 treatment groups. The evaluation of physichochemical performed to measure total acidity, polyphenol, and flavonoid. The sensory evaluation was using hedonic test with untrained panelists and determine score for parameters such as color, aroma, texture, and taste. The results showed that the highest total acidity was 1,06% which found in sample with ratio of rice water and tal palm sap (0:1). However the highest total polyphenol was 15,87 (mg GAE/g) and total flavonoid was 4,52 (mg QE/g) found when the ratio of rice water and tal palm sap similar (1:1). Based on the sensory evaluation, sample with ratio of rice water and tal palm sap (3:1) has the highest score on color was 3,17 ; aroma was 3,00; and taste was 3,00. Accordingly, this study provide data to enhance economical value and product development for tal palm sap.